2008
DOI: 10.1007/s11999-008-0340-2
|View full text |Cite
|
Sign up to set email alerts
|

Synovial Sarcoma: From Genetics to Genetic-based Animal Modeling

Abstract: Synovial sarcomas are highly aggressive mesenchymal cancers that show modest response to conventional cytotoxic chemotherapy, suggesting a definite need for improved biotargeted agents. Progress has been hampered by the lack of insight into pathogenesis of this deadly disease. The presence of a specific diagnostic t(X;18) translocation leading to expression of the unique SYT-SSX fusion protein in effectively all cases of synovial sarcoma suggests a role in the etiology. Other nonspecific anomalies such as over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
64
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(65 citation statements)
references
References 76 publications
0
64
0
1
Order By: Relevance
“…It has an annual incidence of 2.5 per 100,000. It accounts for approximately 8% of all human soft tissue sarcomas [6], and commonly occurs in children and young adults with a male to female ratio of 1.2:1 [7]. Metastatic lesions of the breast only account for 0.5-2% of all breast malignant tumors Characteristics of metastatic breast tumors usually include presence in the superficial tissues and well-defined multinodular masses in the upper outer quadrant of the breast.…”
Section: Discussionmentioning
confidence: 99%
“…It has an annual incidence of 2.5 per 100,000. It accounts for approximately 8% of all human soft tissue sarcomas [6], and commonly occurs in children and young adults with a male to female ratio of 1.2:1 [7]. Metastatic lesions of the breast only account for 0.5-2% of all breast malignant tumors Characteristics of metastatic breast tumors usually include presence in the superficial tissues and well-defined multinodular masses in the upper outer quadrant of the breast.…”
Section: Discussionmentioning
confidence: 99%
“…p53 expression and mitosis of the cases with SYT gene translocation there was no association between p53 expression with mitosis, this is similar as reported by Oda et al 8 This may indicated that p53 signaling pathway was not the only major factor affecting tumor mitosis. Haldar et al 3 explain there are other signaling pathways that influence synovial sarcoma growth. SYT-SSX fusion proteins can increase expression of factors that promote cell proliferation, such as cyclin D1, β-catenin, IGF2, IGF-1R, ERK1, ERK2, p-ERK and can decreased expression of factors that suppress cell proliferation, such as EGR1 and COM1.…”
Section: Oda Etmentioning
confidence: 99%
“…The proportion of both cell are varied and can be classified as several histological subtypes: biphasic subtype, monophasic subtype (monophasic fibrous or rarely monophasic epithelial), and poor differentiated subtype. 3 The tumors contain characteristic translocation t(X;18) (p11.2;q11.2) that produce fusion of SYT gene in chromosome 18 with member of SSX gene family in X damaged cells proliferate and may leads to malignant neoplasms. 5,6 It has been reported that the prognosis associated with mitosis <10/10 HPF (high power field), tumor diameter <5 cm, no necrosis, patients age ≤ 20 years and if tumor can be eradicated by surgery.…”
mentioning
confidence: 99%
“…Currently, synovial sarcoma is thought to arise from undifferentiated mesenchymal cells. Prognosis of synovial sarcoma is poor as the 5-and 10-year survival rates are 36% and 20%, respectively [2].…”
Section: Introductionmentioning
confidence: 99%